A phosphorus-sulfur co-doped hard carbon negative electrode material and its preparation method and application
By using concentrated sulfuric acid and carbon source for heat treatment, the carbonization treatment of hard carbon negative electrode materials is simplified, and a hard carbon negative electrode material co-doped with phosphorus and sulfur is formed, solving the first Coulombic efficiency and ratio of existing hard carbon materials in sodium ion batteries. The problem of insufficient capacity has achieved high specific capacity and high first-term efficiency.
Patent Information
- Application Number
- CN202411551644.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The first time the existing hard carbon materials in sodium ion batteries are low in efficiency and insufficient specific capacity, which limits its practical application in sodium ion batteries.
Concentrated sulfuric acid is used as the sulfur source and catalyst, and the carbonization treatment of the hard carbon anode material is simplified by heat treatment with the carbon source to form a hard carbon anode material co-doped with phosphorus and sulfur.
The specific capacity and first-time Coulomb efficiency of hard carbon anode materials are improved, production energy consumption and cost are reduced, and large-scale production is facilitated.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hard carbon negative electrode materials for sodium ion batteries, in particular to a phosphorus-sulfur co-doped hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Compared with high-cost lithium-ion batteries, sodium-ion batteries have become one of the candidates for large-scale energy storage devices due to their advantages such as abundant resources and low cost. However, compared with lithium ions, sodium ions have a larger ion radius, and the graphite negative electrode widely used in lithium-ion batteries is not compatible with sodium-ion batteries, so other suitable negative electrode materials need to be found. In recent years, the application of hard carbon negative electrode materials in sodium-ion batteries has made great progress.
[0003] Compared with graphite, hard carbon has larger interlayer spacing and more micropores, so it has more sodium storage sites. However, hard carbon still has some shortcomings as a negative electrode material for sodium-ion batteries, such as low first coulombic efficiency and low specific capacity. These shortcomings greatly limit the practical application of hard carbon as a negative electrode material for sodium-ion batteries. In addition, the high specific energy of the battery is one of the important characteristics that people pursue. High specific energy negative electrode materials need to have two characteristics: low sodium desorption potential and high reversible specific capacity. Therefore, it is necessary to improve the specific capacity of hard carbon, especially the capacity of the low-voltage platform section of the charging voltage curve.
[0004] Doping can not only change the electronic structure of hard carbon and enhance the conductivity of hard carbon materials, but also increase active sites. These active sites can serve as adsorption and desorption centers for sodium ions, thereby improving the reactivity and reversibility of sodium ions. In addition, it can optimize the pore structure, such as increasing the number and proportion of micropores and mesopores, improving the connectivity and utilization of pores, and providing more storage space and diffusion paths for sodium ions, ultimately leading to an improvement in the specific capacity and first efficiency of the hard carbon negative electrode.
[0005] For example, the prior art: Chinese patent application No. 202410033157.8 (application publication No. CN 118125414 A) discloses a phosphorus-sulfur co-doped modified hard carbon negative electrode material and a preparation method thereof: a hard carbon precursor is placed in water and mixed to obtain a precursor aqueous solution; a phosphorus source is added to the precursor aqueous solution for cross-linking to obtain a cross-linking solution; a sulfur source is added to the cross-linking solution and mixed to obtain a suspension; the suspension is sequentially dehydrated, solidified and heat-treated to obtain the phosphorus-sulfur co-doped modified hard carbon negative electrode material; the mass percentage of the phosphorus source is 2%-4%; the mass percentage of the sulfur source is 1%-2%. This prior art prepares a P / S co-doped hard carbon structure by cross-linking the phosphorus source with the hard carbon precursor and mixing the sulfur source with the cross-linking solvent. Phosphorus source substances can be used as crosslinking agent curing precursors, which not only help to increase the degree of graphitization and reduce the specific surface area, but also can be used as phosphorus sources to form PC and PO bonds, providing more active sites for the storage of Na / K; the high sulfur-doped hard carbon decomposed from the sulfur source substances easily forms an sp2 carbon skeleton, improves the conductivity and reversible capacity of the hard carbon, thereby improving or even avoiding the problem of low first coulomb efficiency of existing hard carbon materials. However, the above-mentioned dehydration and curing treatment includes: drying and dehydrating the suspension at 60-80°C for 12h, then heating to 120-125°C, pre-curing for 2h, and then heating to 200°C for curing for 2h. The long dehydration time leads to high energy consumption, low production efficiency, and high production cost; curing, i.e. pre-carbonization, is carried out in two steps, and the operation is complicated, which also has an adverse effect on production cost and production efficiency, and is not conducive to large-scale production.
[0006] Providing a low-cost, high initial efficiency, and high specific capacity hard carbon material is of great significance to the development of sodium ion batteries. To this end, this application is proposed. Summary of the invention
[0007] In view of the above-mentioned shortcomings of the prior art, the present invention provides a phosphorus-sulfur co-doped hard carbon negative electrode material and a preparation method and application thereof.
[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0009] First, the present invention provides a method for preparing a phosphorus-sulfur co-doped hard carbon negative electrode material, comprising the following steps:
[0010] S1. crushing and sieving the carbon source;
[0011] S2, mixing the sieved material obtained in the previous step with an aqueous solution of a phosphorus source and placing the mixture in a closed reactor for heat treatment;
[0012] S3, adding concentrated sulfuric acid to the product obtained in the previous step, reacting under stirring, and stopping stirring after the product cools to room temperature after the reaction is completed;
[0013] S4, washing, drying and ball milling the product obtained in the previous step in sequence;
[0014] S5. Carbonizing the product obtained in the previous step under the protection of an inert gas.
[0015] In the preparation method proposed by the present invention, concentrated sulfuric acid is both a sulfur source, providing doping element sulfur for the hard carbon negative electrode material, and a catalyst. Its strong dehydration property enables concentrated sulfuric acid to remove hydrogen and oxygen elements in the carbon source in a ratio of 2:1 when in contact with the carbon source, thereby pre-carbonizing the carbon source. The product after the action of concentrated sulfuric acid can be directly carbonized without pre-carbonization treatment, thereby simplifying the operation, improving production efficiency, reducing production energy consumption and production costs, and being beneficial to large-scale production. Preferably, in step S1, an 80-mesh screen is used for sieving; in step S2, the temperature of heat treatment is 20-100°C and the time is 1-24h; in step S3, the concentrated sulfuric acid is a concentrated sulfuric acid with a mass percentage greater than or equal to 98%; in step S4, washing until the pH of the filtrate is greater than 3 and then drying, ball milling to a particle size Dv50 of 2-20μm; in step S5, the temperature of carbonization is 1000-1600°C and the time is 2-8h.
[0016] The traditional preparation method of hard carbon negative electrode materials is to pre-carbonize and then carbonize. The role of pre-carbonization is to allow the original carbon source to undergo a carbonization reaction under certain temperature and atmosphere conditions to form a carbonaceous conductive network, enhance the mechanical stability of the material, and improve the interface stability between the material and the electrolyte. Pre-carbonization and re-carbonization further deepen the degree of carbonization, so that the material obtains higher conductivity, crystallinity and specific surface area, while optimizing the microstructure such as the stacking method of the carbon layer, the pore structure, etc., and remove residual impurities; pre-carbonization and re-carbonization are two important steps in the preparation of hard carbon negative electrode materials. Pre-carbonization provides a good foundation for carbonization, so that the material can react more fully in the subsequent high-temperature carbonization process to form a more excellent performance. At the same time, re-carbonization is also a further consolidation and improvement of the pre-carbonization effect, so that the material can ultimately meet the performance requirements of the battery.
[0017] The present invention has proved through creative labor that the use of concentrated sulfuric acid as a sulfur source can simplify the carbonization treatment operation of the material while providing doped elemental sulfur for the hard carbon negative electrode material, that is, no pre-carbonization is required, and a hard carbon negative electrode material with excellent performance can be obtained by carbonization in one time. Especially under the above-mentioned technical parameters, the performance of the obtained hard carbon negative electrode material is particularly good.
[0018] It should be noted that:
[0019] (1) In step S1, the particles of the carbon source after crushing should not be too large, as too large a particle size is not conducive to the primary carbonization treatment and results in insufficient primary carbonization. It is preferred to use particles under the sieve of an 80-mesh sieve;
[0020] (2) In step S2, the temperature of the heat treatment is very important for phosphorus-sulfur doping. If the temperature is lower or higher than the specified temperature range, the target doping amount cannot be obtained;
[0021] (3) In step S3, the concentrated sulfuric acid is preferably one with a mass percentage greater than or equal to 98%. The concentrated sulfuric acid in this concentration range has a relatively strong dehydration property and can play a significant pre-carbonization role, providing a good basis for the subsequent re-carbonization treatment. If the mass percentage of the concentrated sulfuric acid is lower than 98%, although it still has a certain dehydration property, the dehydration property becomes weaker, and the pre-carbonization effect will be relatively poor.
[0022] (4) In step S4, if the product is not washed or not washed sufficiently, it will have strong acidity after being treated with concentrated sulfuric acid. Excessive acidity will corrode the surface and internal structure of the hard carbon material, resulting in increased surface roughness of the material, changes in the internal pore structure, damage to the integrity of the material, reduction of its mechanical strength and stability, affecting the electrochemical performance, increasing the interface resistance and causing safety problems. The present invention has found that washing until the pH of the filtrate is greater than 3 and then drying is a preferred operation that effectively avoids the above problems and does not significantly increase the process complexity and processing cost.
[0023] (5) If the carbonization temperature is lower than 1000°C or the carbonization time is lower than 2h, the carbonization of the negative electrode material will be incomplete and insufficient, the pore structure will not be fully formed, and the mechanical properties, thermal stability and electrochemical properties of the material will be poor. If the carbonization temperature is higher than 1600°C or the carbonization time is higher than 8h, it will lead to excessive graphitization of the carbon layer, reduce the number of micropores, and cause the pores to shrink, collapse or block, reduce the active sites for the insertion and extraction of sodium ions, reduce the transmission channels for sodium ions, increase the resistance to the migration of sodium ions, affect the sodium storage performance, rate performance and cycle performance of the material, increase the preparation cost, and easily cause safety problems, such as increased risk of thermal runaway and increased side reactions. The present invention has been found through creative labor that: on the basis of ball milling the product to a particle size Dv50 of 2-20μm in step S4, it can be carbonized at 1000-1600°C for 2-8h to obtain a phosphorus-sulfur co-doped hard carbon negative electrode material with excellent performance.
[0024] Preferably, the carbon source is a biomass carbon source or a sugar, the biomass carbon source is selected from one or more of bamboo, coconut shell, walnut shell, apricot shell, jujube kernel, peach shell, palm shell, tea shell and pine nut shell, the sugar is selected from one or more of sucrose, glucose, starch, cellulose, hemicellulose, chitosan; the phosphorus source is a water-soluble phosphorus source, selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, phytic acid, adenosine triphosphate.
[0025] Preferably, the mass ratio of the phosphorus source to the carbon source is 0.2-1, and the mass ratio of the concentrated sulfuric acid to the carbon source is 0.5-2.
[0026] Taking into account the types of phosphorus source and carbon source, in order to achieve the target doping amount of phosphorus and sulfur and fully ensure the pre-carbonization effect, the present invention finds that when the mass ratio of phosphorus source to carbon source is 0.2-1, and the mass ratio of concentrated sulfuric acid to carbon source is 0.5-2, a hard carbon negative electrode material with excellent performance having a carbon content of 92-99.5wt%, a phosphorus content of 420-2000ppm, and a sulfur content of 20-220ppm can be obtained.
[0027] Secondly, the present invention proposes a phosphorus-sulfur co-doped hard carbon negative electrode material.
[0028] Preferably, the carbon content is 92-99.5 wt %, the phosphorus content is 420-2000 ppm, and the sulfur content is 20-220 ppm.
[0029] Preferably, the phosphorus content is a, the sulfur content is b, and a and b satisfy: 0.55≤(ab) / (a+b)≤0.96.
[0030] After phosphorus doping, PC and PO bonds can be formed, which can provide more active sites for sodium storage and increase the sodium storage capacity, and can also enhance the electrochemical reaction activity and stability of the material; after sulfur doping, the hard carbon material is easier to form an sp2 carbon skeleton, which improves the electrical conductivity and reversible capacity of the hard carbon; moreover, the atomic radii of phosphorus and sulfur are both large, and co-doping can not only effectively widen the carbon layer spacing, which is conducive to the embedding and deintercalation of sodium ions and reduce the embedding barrier, but also promote rapid charge transfer, improve the electronic conductivity of the hard carbon negative electrode, and synergistically improve the electrochemical performance of the hard carbon negative electrode; the synergistic effect of the two improves or even avoids the problem of low first coulomb efficiency existing in existing hard carbon materials, so that the hard carbon negative electrode exhibits higher reversible capacity, better cycle stability and rate performance during the sodium storage process.
[0031] Furthermore, the present invention found that when the phosphorus content a and the sulfur content b satisfy 0.55≤(ab) / (a+b)≤0.96, the performance of the obtained hard carbon negative electrode material is particularly good. It is speculated that at the content limited by this relationship, the synergistic effect of phosphorus and sulfur is more prominent, and therefore the effect of improving the first effect and specific capacity of the hard carbon negative electrode material is more significant.
[0032] Preferably, its specific surface area is 2-15m 2 / g, butanol true density is 1.25-1.5g / cm 3 , particle size Dv50 is 2-20μm.
[0033] The specific surface area is generally required to be smaller to reduce its side reactions with the electrolyte and improve the stability and cycle life of the battery; the true density is an important indicator to measure the density of the hard carbon negative electrode material. A higher true density means a higher energy density and better compaction performance, but it should not be too high. Too high a true density will lead to a decrease in the internal porosity of the material, affecting the diffusion of ions and the penetration of the electrolyte; the particle size Dv50 is another important indicator to measure the density. Generally speaking, a smaller particle size will help to increase the specific surface area of the material and the permeability of the electrolyte, but it may also lead to a decrease in processing performance, while a larger particle size is conducive to improving the tap density and processing performance. Hard carbon negative electrode materials have certain requirements for specific surface area, butanol true density and particle size Dv50. The present invention finds that the hard carbon negative electrode material within the above technical parameter range has both good electrochemical performance and cycle stability and is easy to process.
[0034] Thirdly, the present invention proposes a negative electrode composition for a sodium ion battery, comprising a phosphorus-sulfur co-doped hard carbon negative electrode material.
[0035] The phosphorus-sulfur co-doped hard carbon negative electrode material proposed in the present invention is a negative electrode active material for a sodium ion battery, which is usually used in combination with a conductive agent and a binder to form a negative electrode composition for a sodium ion battery, that is, a negative electrode slurry. The negative electrode composition is coated on a negative electrode current collector to form a negative electrode sheet. Generally speaking, the conductive agent is selected from one or more of conductive carbon black, acetylene black, conductive graphite, Ketjen black, graphene, and carbon nanotubes, and the binder is selected from one or more of sodium carboxymethyl cellulose CMC, styrene-butadiene rubber SBR, polyacrylic acid PAA, polyacrylonitrile PAN, polytetrafluoroethylene PTFE, and polyvinylidene fluoride PVDF.
[0036] Fourthly, the present invention proposes a negative electrode plate for a sodium ion battery, comprising a negative electrode composition for a sodium ion battery and a negative electrode current collector, wherein the negative electrode current collector includes aluminum foil, a conductive polymer, a carbon fiber cloth and other common negative electrode current collectors in the art, and the negative electrode plate is coated with the negative electrode composition on one side or both sides on the negative electrode current collector to form a uniform and dense coating, so as to improve the electrochemical performance and cycle performance of the sodium ion battery.
[0037] Compared with the prior art, the preparation method proposed in the present invention does not require pre-carbonization treatment, so it has low energy consumption, simple operation, high production efficiency, low production cost, and is conducive to large-scale production; under the synergistic effect of specific amounts of doped phosphorus and sulfur, the specific capacity of the obtained hard carbon negative electrode material is improved, and it also has a higher first coulombic efficiency. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0039] It should be noted that the components or structures not described in detail below all adopt conventional technical means in the art or are common knowledge in the art.
[0040] Example 1
[0041] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0042] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0043] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and then placed in a closed reactor, and heat treated at 100° C. for 12 h, with a mass ratio of phosphorus source to bamboo being 0.2;
[0044] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0045] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0046] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0047] Example 2
[0048] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0049] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0050] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 100° C. for 12 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0051] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0052] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0053] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0054] Example 3
[0055] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0056] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0057] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 80° C. for 12 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0058] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0059] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0060] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0061] Example 4
[0062] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0063] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0064] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 80° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0065] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0066] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0067] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0068] Example 5
[0069] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0070] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0071] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 50° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0072] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0073] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0074] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0075] Example 6
[0076] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0077] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0078] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 50° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.8;
[0079] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0080] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0081] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0082] Example 7
[0083] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0084] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0085] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 80° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.8;
[0086] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0087] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0088] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0089] Example 8
[0090] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0091] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0092] S2, mixing the sieve obtained in the previous step with an aqueous solution of ammonium dihydrogen phosphate, placing the mixture in a closed reactor, and heat treating the mixture at 50° C. for 4 h, wherein the mass ratio of the phosphorus source to the bamboo is 1;
[0093] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0094] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0095] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0096] Example 9
[0097] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0098] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0099] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 50° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0100] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 1;
[0101] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0102] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0103] Example 10
[0104] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0105] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0106] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 50° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0107] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 1.5;
[0108] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0109] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0110] Embodiment 11
[0111] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0112] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0113] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 50° C. for 4 h, with a mass ratio of phosphorus source to bamboo being 0.4;
[0114] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 2;
[0115] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0116] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0117] Example 12
[0118] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0119] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0120] S2, mixing the sieve obtained in the previous step with an aqueous solution of ammonium dihydrogen phosphate, putting the mixture into a closed reactor, and heat treating the mixture at 20° C. for 12 h, wherein the mass ratio of the phosphorus source to the bamboo is 1;
[0121] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0122] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0123] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0124] Example 13
[0125] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0126] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0127] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 20° C. for 12 h, with a mass ratio of phosphorus source to bamboo being 0.8;
[0128] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0129] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0130] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0131] Embodiment 14
[0132] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0133] S1, crush the coconut shell with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0134] S2, the sieve obtained in the previous step is mixed with an aqueous solution of ammonium dihydrogen phosphate and placed in a closed reactor, and heat treated at 80° C. for 4 h, with a mass ratio of phosphorus source to coconut shell being 0.8;
[0135] S3, add concentrated sulfuric acid to the product obtained in the previous step, stir well to react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to coconut shell is 0.5;
[0136] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0137] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0138] Embodiment 15
[0139] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0140] S1. Grind the glucose with a mechanical mill and sieve it with an 80-mesh sieve, and retain the sieve residue;
[0141] S2, mixing the sieve obtained in the previous step with an aqueous solution of ammonium dihydrogen phosphate, placing the mixture in a closed reactor, and heat treating the mixture at 80° C. for 4 h, wherein the mass ratio of the phosphorus source to the glucose is 0.8;
[0142] S3, adding concentrated sulfuric acid to the product obtained in the previous step, stirring thoroughly to react, and stopping stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to glucose is 0.5;
[0143] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0144] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0145] Example 16
[0146] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0147] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0148] S2, the sieve obtained in the previous step is mixed with an aqueous solution of phosphoric acid and placed in a closed reactor, and heat treated at 80° C. for 4 h, wherein the mass ratio of phosphoric acid to bamboo is 0.8;
[0149] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0150] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0151] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0152] Embodiment 17
[0153] A method for preparing a phosphorus and sulfur co-doped hard carbon negative electrode material comprises:
[0154] S1, crush the bamboo with a mechanical mill, and sieve it with an 80-mesh sieve, retaining the sieve underfill;
[0155] S2, mixing the sieve obtained in the previous step with the aqueous solution of phytic acid, putting it into a closed reactor, and heat treating it at 80° C. for 4 h, wherein the mass ratio of phytic acid to bamboo is 0.8;
[0156] S3, add concentrated sulfuric acid to the product obtained in the previous step, fully stir and react, and stop stirring after the product cools to room temperature after the reaction is completed. The mass ratio of concentrated sulfuric acid to bamboo is 0.5;
[0157] S4, washing the product obtained in the previous step with deionized water until the pH value of the filtrate is greater than 3, and then drying, and then ball milling with a ball mill until the particle size Dv50 is 2-20 μm;
[0158] S5. The product obtained in the previous step is carbonized under nitrogen protection at a carbonization temperature of 1400° C. for 3 h.
[0159] Comparative Example 1
[0160] Compared with Example 7, the ratio of phosphorus source to carbon source was adjusted to 0.1, and the rest remained the same as Example 7.
[0161] Comparative Example 2
[0162] Compared with Example 7, the ratio of phosphorus source to carbon source is adjusted to 1.2, and the rest is consistent with Example 7.
[0163] Comparative Example 3
[0164] Compared with Example 7, the ratio of concentrated sulfuric acid to carbon source was adjusted to 0.4, and the rest remained the same as Example 7.
[0165] Comparative Example 4
[0166] Compared with Example 7, the ratio of concentrated sulfuric acid to carbon source was adjusted to 2.2, and the rest was consistent with Example 7.
[0167] Comparative Example 5
[0168] Compared with Example 7, the temperature of the heat treatment is adjusted to 10°C, and the rest are consistent with Example 7.
[0169] Comparative Example 6
[0170] Compared with Example 7, the temperature of the heat treatment is adjusted to 120°C, and the rest are consistent with Example 7.
[0171] Comparative Example 7
[0172] Compared with Example 2, step S2 is not performed, that is, phosphorus is not doped, and the rest is consistent with Example 2.
[0173] Comparative Example 8
[0174] Compared with Example 2, step S3 is not performed, that is, sulfur is not doped, and the rest is the same as Example 2.
[0175] Comparative Example 9
[0176] Compared with Example 2, the order of step S2 and step S3 is swapped, and the rest is consistent with Example 2.
[0177] Comparative Example 10
[0178] Compared with Example 2, the 98 wt % concentrated sulfuric acid in step S3 is adjusted to 95 wt % concentrated sulfuric acid.
[0179] Comparative Example 11
[0180] Compared with Example 7, before the operation of step S5, a pre-carbonization treatment is performed, and the pre-carbonization temperature is 400° C., the time is 3 h, and the heating rate is 5° C. / min.
[0181] The specific preparation conditions of the above embodiments and comparative examples are shown in Table 1.
[0182] The hard carbon negative electrode materials prepared in the above embodiments and comparative examples were subjected to ICP test to determine the phosphorus and sulfur contents, and the specific surface area and butanol true density tests were performed at the same time; in addition, negative electrode slurries were prepared as negative electrode active materials, and coated on negative electrode current collectors to form negative electrode sheets, which were further assembled into sodium ion half-cells for electrochemical performance tests. Among them: the negative electrode slurry consists of 90% by mass of negative electrode active materials, 10% of conductive agent Super P, and 10% of binder CMC, and the counter electrode is a sodium sheet; the first effect and specific capacity test temperature is 25°C, the voltage range is 0-2V, and the charge and discharge rate is 0.1C; the phosphorus and sulfur contents are tested by ICP; the specific surface area test. The test results are shown in Table 2.
[0183] Table 1
[0184]
[0185] Table 2
[0186]
[0187] From Table 1 and Table 2, we can see that:
[0188] (1) As shown in Examples 1 to 17, under the preparation conditions specified in the present invention, a phosphorus-sulfur co-doped hard carbon negative electrode material with a first efficiency of 87% or more and a charge capacity of 320 mAh / g can be obtained without pre-carbonization treatment.
[0189] From the comparison of the test results of Comparative Example 11 and Example 7, it can be seen that if pre-carbonization is performed, the first effect and the charge specific capacity are 87.8% and 409.1 mAh / g respectively; if pre-carbonization is not performed, the first effect and the charge specific capacity are 87.7% and 408.7 mAh / g respectively; the preparation method proposed in the present invention performs pre-carbonization before carbonization, which has little effect on the hard carbon negative electrode material, and can even be ignored, so there is no need for pre-carbonization. In addition, whether or not pre-carbonization is performed has little effect on the sulfur content, phosphorus content, specific surface area and butanol true density of the hard carbon negative electrode material, and can be ignored. Obviously, the preparation method proposed in the present invention does not require pre-carbonization, which helps to simplify operations, improve production efficiency and reduce production costs.
[0190] (2) From the comparison of the test results of Comparative Examples 7 and 8 with those of Example 2, it can be seen that if no additional phosphorus or sulfur is added, both the first efficiency and the charge specific capacity are significantly reduced compared with phosphorus-sulfur co-doping.
[0191] Furthermore, in the present invention, the addition amount of the phosphorus source and the sulfur source needs to be controlled within a certain range, which is helpful to obtain a hard carbon negative electrode material with excellent first effect and charge specific capacity. Specifically, the mass ratio of the phosphorus source to the carbon source is 0.2-1, and the mass ratio of the concentrated sulfuric acid to the carbon source is 0.5-2. As shown in Comparative Examples 1 and 2: If the amount of phosphorus source added is too little, it will not only directly lead to a decrease in the amount of phosphorus doping, but also inhibit the doping of sulfur, so that sulfur cannot be doped smoothly, and ultimately affect the charge specific capacity; if the amount of phosphorus source added is too much, it will lead to excessive phosphorus doping and deterioration of the first effect. As shown in Comparative Examples 3 and 4: If the amount of sulfur source added is too little, sulfur doping cannot be achieved, and the pre-carbonization effect cannot be exerted; If the amount of sulfur source added is too much, it will lead to excessive sulfur doping. Although the phosphorus doping amount is within the target doping range, the charge specific capacity performance is not ideal.
[0192] Moreover, the order of phosphorus-sulfur doping is critical. Phosphorus should be doped first, and then sulfur, as shown in the test results of Comparative Example 9 and Example 2: If sulfur is doped first, then phosphorus is doped, under the same conditions, the doping amount of phosphorus decreases significantly, and the first effect and charge specific capacity are significantly deteriorated. It is speculated that the operation sequence of first doping sulfur and then doping phosphorus is not conducive to the smooth doping of phosphorus on the one hand, and on the other hand, it is impossible to give full play to the pre-carbonization effect caused by the strong dehydration of concentrated sulfuric acid, so the electrochemical performance of the obtained product is poor. In addition, the mass percentage of concentrated sulfuric acid is preferably 98% and above. From the comparison of the test results of Comparative Example 10 and Example 2, it can be seen that if 98wt% of concentrated sulfuric acid is adjusted to 95wt% of concentrated sulfuric acid, as the mass percentage of concentrated sulfuric acid decreases, the sulfur doping amount of the obtained product decreases significantly, and the phosphorus doping amount increases significantly, which is limited by the weakening of its dehydration, and the first effect and charge specific capacity are both deteriorated.
[0193] (3) In step S2, the temperature of heat treatment is crucial for phosphorus and sulfur doping. As shown in Comparative Examples 5 and 6, when the heat treatment temperature is 10°C, the amount of sulfur doped in the carbon source is extremely limited, and the amount of phosphorus doped in the carbon source is relatively small; when the heat treatment temperature is 120°C, it will lead to excessive phosphorus doping. In both cases, it is impossible to obtain a hard carbon negative electrode material with excellent first efficiency and charge specific capacity. (4) In combination with the above embodiments and comparative examples, the present invention finds that when a phosphorus-sulfur co-doped hard carbon negative electrode material is used, the phosphorus content is a and the sulfur content is b. When the content range of a is 420-2000ppm, the content range of b is 20-220ppm and a and b satisfy 0.55≤(ab) / (a+b)≤0.96, the electrochemical performance of the obtained product is good. If one of the above conditions is not met, it is impossible to take into account both high first efficiency and high charge specific capacity.
[0194] In summary: the preparation method proposed in the present invention does not require pre-carbonization treatment, so it has low energy consumption, simple operation, high production efficiency, low production cost, and is conducive to large-scale production; under the synergistic effect of specific amounts of doped phosphorus and sulfur, the specific capacity of the obtained hard carbon negative electrode material is improved, and it also has a higher first coulombic efficiency.
[0195] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A method for preparing a phosphorus-sulfur co-doped hard carbon negative electrode material, characterized in that: The steps are as follows: S1. crushing and sieving the carbon source; S2, mixing the sieved material obtained in the previous step with an aqueous solution of a phosphorus source and placing the mixture in a closed reactor for heat treatment at a temperature of 20-100° C. for a time of 1-24 h; S3, adding concentrated sulfuric acid to the product obtained in the previous step, reacting under stirring, and stopping stirring after the product cools to room temperature after the reaction is completed; S4, washing, drying and ball milling the product obtained in the previous step in sequence; S5, the product obtained in the previous step is carbonized under inert gas protection; The carbon source is a biomass carbon source or a sugar, the biomass carbon source is selected from one or more of bamboo, coconut shell, walnut shell, apricot shell, jujube kernel, peach shell, palm shell, tea shell and pine nut shell, the sugar is selected from one or more of sucrose, glucose, starch, cellulose, hemicellulose and chitosan; the phosphorus source is a water-soluble phosphorus source, selected from one or more of phosphoric acid, diammonium dihydrogen phosphate, sodium dihydrogen phosphate, phytic acid and adenosine triphosphate; the mass ratio of the phosphorus source to the carbon source is 0.2-1, and the mass ratio of the concentrated sulfuric acid to the carbon source is 0.5-2.
2. The preparation method according to claim 1, characterized in that: In step S1, an 80-mesh screen is used for sieving; In step S3, the concentrated sulfuric acid is concentrated sulfuric acid having a mass percentage greater than or equal to 98%; In step S4, washing until the pH of the filtrate is greater than 3 and then drying, and ball milling to a particle size Dv50 of 2-20 μm; In step S5, the carbonization temperature is 1000-1600° C. and the time is 2-8 hours.
3. A phosphorus-sulfur co-doped hard carbon negative electrode material prepared according to the preparation method as claimed in claim 1 or 2.
4. The phosphorus-sulfur co-doped hard carbon negative electrode material according to claim 3, characterized in that: The carbon content is 92-99.5wt%, the phosphorus content is 420-2000ppm, and the sulfur content is 20-220ppm.
5. The phosphorus-sulfur co-doped hard carbon negative electrode material according to claim 4, characterized in that: The phosphorus content is a, the sulfur content is b, and a and b satisfy: 0.55≤(ab) / (a+b)≤0.
96.
6. The phosphorus-sulfur co-doped hard carbon negative electrode material according to claim 3, characterized in that: Its specific surface area is 2-15m 2 / g, butanol true density is 1.25-1.5g / cm 3 , particle size Dv50 is 2-20μm.
7. A negative electrode composition for a sodium ion battery, characterized in that: A phosphorus-sulfur co-doped hard carbon negative electrode material comprising the phosphorus-sulfur co-doped hard carbon negative electrode material as described in any one of claims 3 to 6.
8. A negative electrode plate for a sodium ion battery, characterized in that: The invention comprises the negative electrode composition for a sodium ion battery as claimed in claim 7 and a negative electrode current collector.
Citation Information
Patent Citations
Hard carbon composite material, preparation method and application thereof, and lithium ion battery
CN115425221A
Phosphorus-sulfur co-doped modified hard carbon negative electrode material and preparation method thereof
CN118125414A
Cited By
Hard carbon material for fast-charging sodium ion battery and preparation method thereof
CN122627417A
Asphalt-based hard carbon material for sodium-ion battery negative electrode and preparation method thereof
CN122916104A